Monkeypox: A Comprehensive Analysis of The Virus and its Implications for Public Health - Ibrahim, Dhafer Faeq; Hamad, Rokan Hazim; Abdullah, Sadoon Mohammed (Central Asian Journal of Medical and Natural Science, 2025)
Monkeypox (MPX) is a contagious disease caused by a virus related to smallpox. First discovered in the Democratic Republic of the Congo in 1970, it has historically affected parts of West and Central Africa. However, the World Health Organization declared a global health emergency in July 2022 due to its unprecedented spread to Europe, North America, and Oceania, which has raised international concern. The disease poses a significant public health issue, partly because over 70% of the global population is no longer vaccinated against smallpox, which also provides some protection against monkeypox. Despite advancements in treatments and diagnostics, monkeypox continues to cause severe health and economic impacts, with over 85,000 cases reported by January 2023. Vaccines are currently used against monkeypox: two are smallpox vaccines repurposed for monkeypox, and the third is designed for biological threats. The first vaccine is a non-replicating smallpox vaccine suitable for people with weakened immune systems. The second, ACAM2000, is a second-generation smallpox vaccine recommended for monkeypox prevention but not for people with certain health conditions or during pregnancy. The third, LC16M8, is a modified smallpox vaccine aimed at reducing side effects while generating broad immune responses. The effectiveness of these vaccines against the current outbreak remains uncertain. There is a need for new, safer vaccines, with some experts suggesting that vaccines targeting specific immune responses might be more effective. This review seeks to provide updated information on the epidemiology, clinical features, diagnosis, management, and prevention of monkeypox.